Meteorological expressions in Basque grammar and the Theory of Grammar - Iñigo Arteatx; Xabier Artiagoitia (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2018)
This article makes two claims with respect to meteorological expressions in Basque grammar: firstly, it shows that, in the light of Eriksen, Kittilä and Kolehmainen's (2010) crosslinguistic typology of metereological expressions, Basque resorts to the so-called argument type (and less frequently to the predicate-argument split type) when coding precipitation and dynamic events and to both the argument and the predicate type when coding other methereological events; it is worth noting that Basque uses transitive structures in many cases, a rare feature typologically speaking. Secondly, regarding two key issues in the study of weather predicates within Generative Grammar, the article claims (a) that Basque supports the view that both lexicalizations of weather verbs (unacussative and unergative/transitive) are possible across languages, as argued by Bleotu (2015); and (b) that the empy pro subject of Basque transitive weather constructions has the features of a quasi-argument (Chomsky 1981, Krejci 2014) rather than those of an expletive.